Edna Pontellier: una ou múltipla? - Rodrigues, Thalita Raquel de Carvalho (2016)
The focus of our research is on Edna Pontellier, the protagonist of The Awakening, a 19th century novel whose main character is a housewife who was in search of her own emancipation. Our theory and critical resources are supported by works written by Per Seyersted(1979) and Nadilza Moreira(2003) both references names for Chopin's scholarship.Besides, we used Beauvoir' (1970), Woolf' (2012) and Showalter's(1979) critical studies to help us to develop our understanding of the 19th century social-hisorical women's context in the USA. For the study of representation we used the concept fromAna Gabriela Macedo e Ana Luisa Amaral(2005). To support our analysis on the role of the narrative voice we used Chris Baldick(1991) Our conclusion is that: Edna Pontellier represents a multiplicity of images and they are presented to the reader as the narrative develops itself showing Edna's multiples “awakenings” as a woman in transition.